Qualitative Modeling of Spatial Orientation Processes and Concurrent Reference Frame Conflicts using Logical Propositions - Riecke, Bernhard E. (International Workshop on Models and Representations in Spatial Cognition, 2016)
While navigation in the real world can already be difficult enough, this challenge tends to increase for travel through imagined or computer-mediated environments like virtual environments and tele-presence applications. We propose that this can, at least in part, be attributed to a concurrent reference frame conflict in working memory between one’s automatically activated primary embodied egocentric representation of one’s immediate physical environment on the one hand and the additional 1st person (egocentric/embodied) reference frame provided by the computer-mediated or imagined environment on the other hand. Here, we will use a visually presented framework that integrates logical propositions (i.e., necessary and sufficient conditions) to discuss different underlying processes and implications. For example, we propose that alignment (and thus lack of interference) between concurrent egocentric reference frames is a necessary prerequisite for a number of desirable spatial orientation characteristics such as ease of adopting a new perspective, low cognitive load, and automatic spatial updating. Conversely, we propose that increasing concurrent reference frame conflict can lead to increased cognitive load, difficulty of perspective changes, impaired spatial updating, and thus reduced task performance in numerous applications such as telepresence or motion simulation in VR.
Keywords: BeMa model; NSERC DG 2026; Riecke; Riecke_2016; bernhard-riecke; invited talk; logical model; talkWithoutPaper; theoretical framework